Sustainable Development Goal (SDG) 16 (peace, justice and effective institutions) and access to justice in Brazil (Revista Direitos Humanos e Democracia, 2025)
In 2015, the United Nations (UN) established 17 Sustainable Development Goals (SDGs) to address today's main global challenges. These goals gave rise to the "2030 Agenda", which committed the countries participating in the United Nations Summit on Sustainable Development, including Brazil. The 2030 Agenda has become the main guideline for the formulation and implementation of public policies by governments around the world. This text intends to answer the following question: is the evaluation of national judicial policies for access to justice an instrument that can bring effectiveness to the Brazilian Judiciary and, consequently, contribute to the fulfillment of the Sustainable Development Goal - SDG 16 (Peace, Justice and Effective Institutions), especially in the light of goal 16.3 (promote the rule of law and ensure equal access to justice)? The general objective is to verify whether the evaluation of national judicial policies on access to justice is an instrument that can bring effectiveness to the institutions of the Brazilian justice system and, consequently, contribute to the fulfillment of SDG 16, especially in light of target 16.3. To address this issue, the deductive method was used. The procedure adopted was the monographic. In the end, it is concluded that, in order to affirm that SDG 16 and its target 16.3 have been effectively fulfilled in the implementation of the mechanisms for access to justice in Brazil, it is necessary that the users of the justice system continuously evaluate this access, in order to correct possible failures and solve the weaknesses.
Keywords: access to justice; evaluation; SDG 16; public policy; judicial policy